Application of Rh/MWCNT catalysts in the preparation of conjugated linoleic acid from linoleic acid. Issue 9 (6th June 2021) - Yu, Dianyu; Cheng, Jie; Wang, Ning; Li, Ziyue; Chen, Xing; Wu, Fei; Yang, Fuming; Wang, Liqi
Abstract: The Rh/MWCNT catalyst was prepared by the impregnation method and linoleic acid in conjugated evening primrose oil was used to generate conjugated linoleic acid (CLA). The supported metal catalyst was prepared by the impregnation method and the catalyst was characterized by transmission electron microscopy (TEM), energy‐dispersive X‐ray spectroscopy (EDX), X‐ray diffraction (XRD), and N2 ‐adsorption‐desorption. When the catalyst loading was 0.7 wt%, the catalytic activity was 90.31%. When the catalyst addition amount was 5%, the stirring speed was 600 r/min, the reaction time was 4 hr, and the reaction temperature was 180℃, the CLA yield was 67.12%, the conjugate product was mainly two CLA isomers, and the trans acid (TFA) content was only 1.21%. The catalyst has good catalytic performance and can be reused five times. Practical applications: To meet the industrial needs of conjugated linoleic acid, an Rh/MWCNT catalyst was synthesized by a simple method. The metal rhodium‐based catalyst successfully converted linoleic acid in monthly grass oil to conjugated linoleic acid. The results show that rhodium‐based catalysts have good catalytic properties, have specific application prospects in the field of catalysis, and provide a theoretical basis for the production of conjugated linoleic acid.